2017
DOI: 10.1371/journal.ppat.1006668
|View full text |Cite
|
Sign up to set email alerts
|

Merkel cell polyomavirus recruits MYCL to the EP400 complex to promote oncogenesis

Abstract: Merkel cell carcinoma (MCC) frequently contains integrated copies of Merkel cell polyomavirus DNA that express a truncated form of Large T antigen (LT) and an intact Small T antigen (ST). While LT binds RB and inactivates its tumor suppressor function, it is less clear how ST contributes to MCC tumorigenesis. Here we show that ST binds specifically to the MYC homolog MYCL (L-MYC) and recruits it to the 15-component EP400 histone acetyltransferase and chromatin remodeling complex. We performed a large-scale imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
125
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(129 citation statements)
references
References 81 publications
(110 reference statements)
4
125
0
Order By: Relevance
“…Thus, we analyzed LT expression and its size by immunoblotting for all nine MCC cell lines, i.e., our six cell lines as well as MKL‐1, MKL‐2 and MS‐1. This analysis was performed with a monoclonal antibody which recognizes the common protein sequence of sT and LT (clone AB5;). All cell lines demonstrated expression of truncated LT (tLT) (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Thus, we analyzed LT expression and its size by immunoblotting for all nine MCC cell lines, i.e., our six cell lines as well as MKL‐1, MKL‐2 and MS‐1. This analysis was performed with a monoclonal antibody which recognizes the common protein sequence of sT and LT (clone AB5;). All cell lines demonstrated expression of truncated LT (tLT) (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…n.d.: not done. 10 Indicates whether complete amplification of integrated MCPyV was possible. 11 Accession numbers for the cells lines established by us were uploaded to NCBI.…”
Section: Identification Of Integration Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, mutations in Aa occur at high frequency in premalignant endometrial lesions (Anglesio et al 2017). PP2A is also a target of the Small T antigens (ST) of SV40 and other polyomaviruses including the human oncogenic Merkel cell polyomavirus (Pallas et al 1990, Chen et al 2004, Cheng et al 2017) and this interaction contributes to cell transformation (Hahn et al 2002). Structural studies have shown that ST disrupts formation of a functional PP2A holoenzyme by displacing or hindering B subunit access to the PP2A core-enzyme (Chen et al 2007, Cho et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Current understanding suggests that LT and sT are the major oncoproteins mediating MCPyV‐driven tumorigenesis. Truncated MCPyV‐LT binds and inactivates pRB, while sT stabilizes and augments the activity of key oncoproteins including MCPyV‐LT and MYCL, among others . Further clarification of the mechanisms by which these viral oncoproteins promote tumorigenesis will suggest future targets for therapy.…”
Section: Introductionmentioning
confidence: 99%